2015
DOI: 10.1038/ki.2015.72
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroidectomy and survival among Japanese hemodialysis patients with secondary hyperparathyroidism

Abstract: Parathyroidectomy (PTx) drastically improves biochemical parameters and clinical symptoms related to severe secondary hyperparathyroidism (SHPT) but the effect of PTx on survival has not been adequately investigated. Here we analyzed data on 114,064 maintenance hemodialysis patients from a nationwide registry of the Japanese Society for Dialysis Therapy to evaluate the associations of severity of SHPT and history of PTx with 1-year all-cause and cardiovascular mortality. We then compared the mortality rate bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
132
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 42 publications
6
132
0
2
Order By: Relevance
“…Moreover, Komaba et al (26) studied the effect of parathyroidectomy on survival in patients with severe sHPT. They compared mortality among patients who underwent parathyroidectomy and propensity score-matched patients who did not undergo parathyroidectomy, despite severe sHPT, and suggested that parathyroidectomy reduced the risk for all-cause and cardiovascular mortality in patients with severe sHPT (26).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Komaba et al (26) studied the effect of parathyroidectomy on survival in patients with severe sHPT. They compared mortality among patients who underwent parathyroidectomy and propensity score-matched patients who did not undergo parathyroidectomy, despite severe sHPT, and suggested that parathyroidectomy reduced the risk for all-cause and cardiovascular mortality in patients with severe sHPT (26).…”
Section: Discussionmentioning
confidence: 99%
“…Of them, 37 studies were retrieved for detailed evaluation, and finally 24 studies were excluded due to absence of information on the outcomes of interest (19 articles) or provision of data only in abstract form (5 articles). Finally, 13 studies [19][20][21][22][23][24][25][26][27][28][29][30][31] fulfilled the eligibility criteria ( Figure 1), with 10052 PTx-treated patients and 12001 medically-treated patients (totally 22053 patients). The 13 studies were all cohort studies with sample sizes from 20 to 4558 patients, and reported prevalence rates of diabetes from 0% to 44.3%.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…Most studies adjusted a wide range of potential confounders to investigate the association between PTx and all-cause mortality, including age, sex, body mass index (BMI), diabetes, duration of dialysis, and dialysis modality. Twelve studies presented data with all-cause mortality [19][20][21][22][23][24][25][26][27][28][29]31 and six studies with cardiovascular mortality. 19,20,23,26,28,30 Table 1 lists the key characteristics of the 13 studies.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term effects of cinacalcet therapy on hard outcomes in kidney transplant recipients are unknown at present. As to parathyroidectomy, a recent observational study reported that it was associated with improved survival in patients on maintenance dialysis, which was also shown by one of us before 13 but not in patients with a renal allograft. 14 Another issue lacking consensus is the relative merit of subtotal compared with total parathyroidectomy.…”
mentioning
confidence: 67%